Efeito de vernizes contendo Xilitol na remineralização do esmalte de dentes permanentes jovens: estudos in vitro e in situ. - Siqueira, Vanessa Lira (2019)
Xylitol, a sugar substitute, has gained attention in the last years due to its bacteriostatic, anticaries and remineralizing properties. Considering that the varnish containing sodium fluoride is a widely used strategy in dentistry for dental caries control, the present study had the objective to evaluate the remineralization capacity of the enamel from young permanent teeth by a new varnish containing xylitol at 20%, with different particle sizes (146 and 80μm). The study was performed in two stages, one in vitro (Phase 1) and another in situ (Phase 2). The initial surface hardness was performed on 120 specimens (4x4 mm) that were submitted to the induction of artificial caries lesion (Buskes solution, 11 days), and the hardness after demineralization was again performed. The specimens were randomly assigned according to the mean hardness mean after demineralization in 4 groups: a) varnish with 20% xylitol; b) varnish with 20% ground xylitol; c) Duraphat® varnish - positive control and d) placebo varnish - negative control in both Phase 1 and Phase 2 (n = 15 specimens per group). The varnishes were applied in a thin layer on the specimens and removed after 6 hours of artificial saliva immersion. In Phase 1, the groups were submitted to pH cycling (demineralization-2h / remineralization-22h per day) over a period of 8 days and, at the end, the percentage of surface hardness recovery (%SHR), subsurface hardness and integrated mineral loss (ΔKHN) were evaluated. In Phase 2, 15 individuals participated in the double blind study and used palatal appliances containing 4 previously demineralized specimens. Each specimen received the application of one of the 4 types of varnishes: a, b, c or d, as previously mentioned. Data were analyzed statistically by Kruskal-Wallis/ANOVA and Tukey post hoc tests (p˂0,05). The values of %SHR were significantly higher for the experimental varnishes containing xylitol and the gold standard varnish when compared to the placebo varnish, and did not differ significantly between them. Regarding the integrated mineral loss, the experimental and commercial varnishes showed significantly lower lesion areas compared to the placebo varnish, not differing from each other. The reduction of xylitol particle size by 45% decreased its precipitation in the experimental varnish, but did not influence the remineralizing capacity of the material. The varnishes containing xylitol appear to be promising alternatives in the promotion of dental enamel remineralization of young permanent teeth both in vitro and in situ.